NATURE AND MAN: THE FOUNDATIONS OF SPIRITUAL AND ETHICAL COOPERATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This paper explores the significance of ecological consciousness and cultural values in the protection of the environment. In the context of growing environmental challenges, the formation of ecological ethics and environmentally responsible behavior is becoming increasingly important. The study emphasizes the role of education, traditional cultural practices, and moral awareness in fostering a sustainable attitude toward nature. Special attention is given to the integration of ecological values into social norms and the development of an environmental culture that promotes responsible interaction with the natural world. The findings highlight that protecting the environment is not only a technical or legal issue but also a deeply moral and cultural responsibility.